High Burden of Staphylococcus aureus Among Native American Individuals on the White Mountain Apache Tribal Lands. (22nd February 2020) - Sutcliffe, Catherine G; Grant, Lindsay R; Reid, Angelina; Douglass, Grace; Brown, Laura B; Kellywood, Kamellia; Weatherholtz, Robert C; Hubler, Robin; Quintana, Alvaro; Close, Ryan; McAuley, James B; Santosham, Mathuram; et al.
Abstract: Background: This study was done to determine the burden of invasive Staphylococcus aureus on the White Mountain Apache Tribal lands. Methods: Active population and laboratory-based surveillance for invasive S aureus infections was conducted from May 2016 to April 2018. A case was defined as a Native American individual living on or around the White Mountain Apache Tribal lands with S aureus isolated from a normally sterile body site. Results: Fifty-three cases were identified. Most cases were adults (90.6%) and had ≥1 underlying medical condition (86.8%), the most common of which were diabetes (49.1%) and obesity (41.5%). A total of 26.4% cases were categorized as community acquired. Most infections were methicillin-resistant (75.5%). A total of 7.5% of cases required amputation, and 7.7% of cases died within 30 days of initial culture. The incidence of invasive S aureus was 156.3 per 100 000 persons. The age-adjusted incidence of invasive methicillin-resistant S aureus was 138.2 per 100 000 persons. Conclusions: This community has a disproportionately high burden of invasive methicillin-resistant S aureus compared with the general US population. Interventions are urgently needed to reduce the morbidity and mortality associated with these infections.